2011
DOI: 10.2215/cjn.01260211
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Mediated Vasodilation in End-Stage Renal Disease

Abstract: SummaryBackground and objectives An intact endothelium is essential for adaptations between arterial vasomotor tone and shear stress (SS), i.e., flow-mediated vasodilation (FMD). Endothelial dysfunction occurs in hypertension, cardiac insufficiency, diabetes, atherosclerosis, and in end-stage renal disease (ESRD) patients, whose renal failure is associated with many of those cardiovascular diseases (CVD).Design, setting, participants, & measurements Using a progressive hand-warming protocol and repeated measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…CRP C-reactive protein, IL-6 interleukin-6, NO nitric oxide, PAI-1 plasminogen activator inhibitor 1, PGI2 prostacyclin, sICAM soluble intercellular adhesion molecule, sVCAM soluble vascular cell adhesion molecule, TNF-α tumour necrosis factor alpha, vWF von Willebrand factor function in this CKD cohort is similar to what others have shown using both venous occlusion plethysmography techniques [43], and FMD [44]. Owens et al [45] determined FMD among 25 CKD patients prior to AVF creation and found very similar values (5.8 ± 1.0%).…”
Section: Endothelium Dysfunction and Avf Maturationsupporting
confidence: 86%
“…CRP C-reactive protein, IL-6 interleukin-6, NO nitric oxide, PAI-1 plasminogen activator inhibitor 1, PGI2 prostacyclin, sICAM soluble intercellular adhesion molecule, sVCAM soluble vascular cell adhesion molecule, TNF-α tumour necrosis factor alpha, vWF von Willebrand factor function in this CKD cohort is similar to what others have shown using both venous occlusion plethysmography techniques [43], and FMD [44]. Owens et al [45] determined FMD among 25 CKD patients prior to AVF creation and found very similar values (5.8 ± 1.0%).…”
Section: Endothelium Dysfunction and Avf Maturationsupporting
confidence: 86%
“…As others have elegantly described, endothelial dysfunction and inflammation are likely synergistic precursors to diastolic dysfunction. (28, 29) CKD exemplifies a disease state of endothelial dysfunction (30) and inflammation (31) and thus CKD may be an especially appropriate population to study associations between endothelial dysfunction, inflammation, and abnormal systolic and diastolic cardiac mechanics. Further studies of inflammatory mediators in these patients might clarify the role of inflammation in the associations that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…FMD of the brachial artery was assessed noninvasively using high-resolution ultrasound as described previously in detail [17,18,19]. For patients on hemodialysis, measurements were obtained before the first hemodialysis of the week.…”
Section: Methodsmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) kit for the detection of PDMPs [17,18,19] was obtained from JIMRO Co. Ltd. (Tokyo, Japan) as described previously in detail [20,21]. Briefly, a blood sample was collected from an arteriovenous fistula into a vacutainer containing ethylenediaminetetraacetic acid-acid citrate dextrose solution (EDTA-ACD; Nipro Co. Ltd., Japan).…”
Section: Methodsmentioning
confidence: 99%